LIDERAZGO Y EL ROL DEL TRABAJADOR SOCIAL EN LA ASOCIACION DE DISCAPACITADOS VISUALES DE LA PROVINCIA DE LOJA - Mónica Janeth, Albarracín Erreis (2016)
Leadership is the function that takes a person apart from the rest and is able to make sound decisions for the group, team or organization that precedes, inspiring the rest of those involved in that group to achieve a common goal. For this reason, it is said that leadership involves more than one person, who runs (the leader) and those who support (subordinates) and allow it to develop its position efficiently. At present, members of the Association of the Visually Handicapped of the Province of Loja, are affected by the lack of opportunities that are denied social environment, this brings consequences multiple problems affecting the daily life and the partners and therefore of their family, but especially for improvement. There is an important factor that affects the lack of opportunity and discrimination and prejudice produced by the company, which makes people blind and self limitations in family interaction. Thus, this research was framed in the wonderful world of leadership and the role that we play as Social Workers and which will have to penetrate the work of Visually Impaired Association of the Province of Loja, same as it is fully regularized with Ministerial Agreement N-069, this has been 8 working for about 12 years for people with visual impairments, this first was formed as pre-association, from there its leaders have been planning and developing activities that benefit members. At the Association we have found that the leadership exercised effective leadership and that there is full cooperation on the part of its members, through this participation, they have been able to achieve some success as authorized by Municipal Ordinance for the installation and operation of kiosks at strategic sites in the city in order to generate employment and occupation for people with disabilities, and to expend the same cards SIMERT and increased profits by selling these from 5% to 15%, this was a Lojano management before the council. This action benefits to members and people with distinctive capabilities in general. Another important achievement for the Association is the project called "Copying Our Future" aimed at generating employment and occupation for members of the association. Perhaps the most significant achievement for the life of the Association has been the financing of the Project for Education and Economic and Social Inclusion for People with Visual Impairment in the Province of Loja first and second stage, achieving blind Literacy cantons: bald, Espindola, Sozoranga, Avocado and Loja (San Lucas) and the insert to family 9 production processes as an alternative to access to employment and occupation. With all these important actions of the Association leaders have managed to position your organization in the collective citizen, generating welfare to its members and seeking an advance positive, as you say them, no more begging, no more hurt, if more honest work for try to achieve a breakthrough for our Association and especially to our beloved Loja. To achieve all these achievements have had to strengthen the leadership skills to direct, guide and strengthen the collective effort towards continuous innovation and adaptation of new social circumstances. Among the objectives we have set, these have been met and have allowed some way contribute to strengthening the Visually Impaired Association of the Province of Loja, through the Design of Organizational Strengthening Plan, considering effective leadership within of the leadership. In the field of research and methodology, the study on its quantity and quality also was oriented to the implementation of twenty surveys , corresponding to one hundred percent of the members of the Association of the Visually Handicapped of the Province of Loja , in this study data 10 obtained concrete, real and updated elements that explain the level of leadership of the leaders of this Association , factor in the socio - organizational same as: within the organization do not maintain a good working relationship because the lack of interest of the members in the activities carried out within the institution , also the leadership does not care about creating a harmonious environment in which to engage its partners . Another factor in organizational development is the inadequate attention given by the association , the provision of quality services are not , they are made with little affection and almost no teamwork . The leadership does not exercise good leadership, because no efforts are made to train professionals in various branches of the members of the association. Internally there is little motivation, aptitude and ability to influence others, made weak leadership exists in this institution. Another important factor regarding the leadership, because she is not trained enough to assume their rightful role. Under these circumstances, all the investigative process the majority of the members of the organization are committed to collaborate in all activities, and the development and implementation of socio-building plan - organization, that through this seeking training and improve their living conditions. 11 Then we can say that for us as future social workers, this process has been very significant for the achievement of our goals, and we see that in life nothing is impossible, and we had the opportunity to link classroom learning with professional practice and most especially we achieved all the objectives in this research work.